The Coupling Characteristics of Vapor Pressure Deficit and Soil Moisture in China - Chong Nie; Chunxu Hao; Xingan Chen; Juan Zhou; Rui Xu; Chenning Deng; Zeqian Zhang; Yanzhong Zhu; Lijing Wang (Remote Sensing)
Vapor pressure deficit (VPD) and soil moisture (SM) are the two main parameters related to ecosystem water stresses. They are tightly coupled through land–atmosphere interactions and have large impacts on terrestrial ecosystems and global water and carbon cycles. However, the coupling characteristics between the two have not been thoroughly studied, particularly in the context of climate warming. In this study, based on remote sensing and reanalysis datasets, spatial and temporal variations in the VPD and SM and their correlation coefficients in the growing season in China from 1982 to 2018 were evaluated. Then, the probabilities of compound water stress (high VPD and low SM) were investigated under three scenarios based on a copula analysis. The results show that, over the 37 years, the VPD significantly increased during the growing season, while the SM significantly decreased. The coupling relationship between the VPD and SM was relatively weak in extreme arid and arid regions. In contrast, this relationship was stronger in semi-arid and semi-humid regions, where the probabilities of compound water stress were significantly higher (p < 0.05). The probabilities of compound water stress (high VPD and low SM) were significantly higher than the probabilities when the VPD and SM were independent, and this difference increased with the severity of the water stress in the same region. The obtained results can be further applied to improve Earth system models and formulate agricultural irrigation schemes.